Batik Jlamprang Pekalongan Dance as Character Education Media for Early Childhood in Kindergarten B TK Batik Pencongan, Wiradesa, Pekalongan - Astuti, Febri; arum eka, Agustinus (Jurusan PGPAUD FIP UNNES, 2017)
The impact of globalization that is happening today brings Indonesian society to forget the character education of the nation. This study is based on the phenomenon of violence in children. Based on data from Tempo.co news uploaded on Wednesday 28 September 2016 declared a four-year-old Elderly Student in Wates Sub-district to be the victim of brutal brutal persecution of her class. This study aims to reveal the value of character education values ​​contained in Jlamprang Pekalongan Batik dance and Jlamprang Pekalongan Batik dance as a medium of character education in kindergarten B TK Batik Pencongan Wiradesa Pekalongan. This research use desciptive qualitative approach. Based on the results of this research is Batik Jlamprang Dance as a medium of character education is given as a means to achieve learning objectives. Implementation of character education is done through the process of planning, learning and habituation. Through this Jlamprang Batik Dance learning, it is expected that children can grow the character of patience, independence and hard work and change the character of the child from the bad to be good.